Lubricity of paraffinic fuels additivated with conventional and non-conventional methyl esters. (September 2019) - Rodríguez-Fernández, José; Ramos, Angel; Sánchez-Valdepeñas, Jesus; Serrano, Jose Ramon
Fuel lubricity prevents wear between metallic parts in relative motion inside the injection system of combustion engines. Among diesel fuels, paraffinic (gas-to-liquid or hydrotreated oils) and biodiesel (methyl esters) fuels are emerging since some of them are renewable and, in the case of paraffinic fuels, present excellent properties that can be exploited in compression ignition engines. However, the lubricant properties of raw paraffinic fuels are poor. This work explores the potential of individual methyl esters, found in different biodiesel fuels derived from a wide variety of sources, as lubricity additives for paraffinic fuels. Blends at 1% and 2% ester content in a surrogate of paraffinic fuel were tested under the standardized high-frequency reciprocating rig test for lubricity determination. Results confirm the extremely poor lubricity of the surrogate and that the wear scar diameter measured (the higher this, the lower the fuel lubricity) can be significantly reduced with any of the tested esters just at 1% concentration. Higher ester concentration (2%) does not always improve the lubricity further. The number of double bonds in the ester was revealed very significant, but to boost the lubricity of the blend and fulfill the limits set in fuel quality standards, two or more polyunsaturated esters are necessary.